2007
DOI: 10.3174/ajnr.a0594
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Damage But No Increased Glial Cell Activity in the Normal-Appearing White Matter of Patients with Clinically Isolated Syndromes Suggestive of Multiple Sclerosis Using High-Field Magnetic Resonance Spectroscopy

Abstract: BACKGROUND AND PURPOSE: Proton MR spectroscopy ( 1 H-MR spectroscopy) is a well-established method for the in vivo investigation of the normal-appearing white matter (NAWM) in patients with multiple sclerosis (MS). Metabolic changes in NAWM are of special interest in patients with clinically isolated syndromes (CIS) suggestive of MS regarding further prognostic classifications. The purpose of this study was to investigate metabolic alterations in NAWM in patients with CIS with use of high-field 1 H-MR spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 39 publications
7
43
1
Order By: Relevance
“…4,6 The entire brain parenchyma seems not affected (continuously) in patients with NMO. 1,26 In contrast to NMO in classic RRMS, even in very early disease stages, axonal metabolic changes and damage might be found in a subgroup of patients with RRMS, 27 whereas in other patients with RRMS, NAA levels are normal and remain stable for years (F.A.-.E., unpublished data; 2007-2009; manuscript in preparation). 28 Our MR spectroscopy data confirm the previous observation of Bichuetti et al, 26 who studied 16 patients with NMO and 16 controls, and the clinical observations found by others and ourselves.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 The entire brain parenchyma seems not affected (continuously) in patients with NMO. 1,26 In contrast to NMO in classic RRMS, even in very early disease stages, axonal metabolic changes and damage might be found in a subgroup of patients with RRMS, 27 whereas in other patients with RRMS, NAA levels are normal and remain stable for years (F.A.-.E., unpublished data; 2007-2009; manuscript in preparation). 28 Our MR spectroscopy data confirm the previous observation of Bichuetti et al, 26 who studied 16 patients with NMO and 16 controls, and the clinical observations found by others and ourselves.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that axonal damage is constantly detected in patients with definite MS, first evidence for axonal damage already occurring during the first demyelinating episode has been reported in NAWM of CIS patient group with a longer median disease duration and by a whole brain MR spectroscopy analysis incorporating lesions as well as normal appearing brain tissue [32,38]. In addition to this, the significantly decreased tNAA concentrations in our study are highly indicative for a substantial axonal damage even in the NAWM of CIS patients with disease duration of approximately one month.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration values and ratios in our healthy control group have been described in detail elsewhere [32]. Typical spectra from a patient presenting with CIS and from a healthy control are illustrated in Fig.…”
Section: ■ 1 H-mrsmentioning
confidence: 99%
“…Recently published single voxel 1 H-MRS studies in CIS patients including an optimized acquisition protocol for tNAA and mIns (short and long echo time acquisition) demonstrated that axonal damage is already present in CIS patients not fulfilling the criteria for definite MS [74]. A significant increase of mIns could be observed in patients with an early disease course of relapsing-remitting MS but not in patients presenting with a CIS.…”
Section: Quantitative Mri Methodsmentioning
confidence: 99%